ANALISIS AKIBAT HUKUM PERCERAIAN TERHADAP HARTA BERSAMA DI PENGADILAN AGAMA SEMARANG (STUDI KASUS PUTUSAN PENGADILAN AGAMA NOMOR 3122 TAHUN 2019) - Indra Cahyaning Widhi Siswoyo; Arikha Saputra (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2022)
This study aims to determine the legal consequences of divorce on the distribution of joint property and to find out and analyze the judge's considerations in passing a divorce decision on the distribution of joint property. This study uses a normative juridical writing method sourced from literature studies. The writing data presented in the descriptive analysis of this analysis will then be analyzed using qualitative methods. The legal consequences of divorce on the distribution of joint assets are based on the provisions of Law Number 1 of 1974 concerning Marriage, namely in article 37, the Civil Code (KUHPerdata), precisely in articles 126-128. Regarding the Judge's Consideration in Imposing Divorce Decisions on the Distribution of Joint Assets in the case decision Number 3122/Pdt.G/2019/PA.Smg the panel of judges has been fair and observant in looking at the existing series of cases. other than that, the judge's consideration is based on Article 1 letter f of the Compilation of Islamic Law.